E-learning Academy Untuk Meningkatkan Kapasitas SDM Di Lingkungan Perusahaan Transportasi X - Andarsyah, Roni; Prianto, Cahyo (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
Services in the field of land transportation services are still a sector needed by the community for mobility and economic growth. The main problem faced by Transportation Company X in developing human resources (HR) is the uneven skills and knowledge between generations in the organizational structure. Gen X dominates with 57.36%, Gen Y (38.34%) and Gen Z (4.29%). This has an impact on the ability to adapt to the demands of the modern transportation industry. This research aims to develop and implement an e-Learning Academy, to increase the capacity of X Transportation Company's human resources. This research methodology uses SCRUM framework in learning system development, with agile approach that allows adaptation to changes quickly and efficiently. E-Learning Academy features video-based learning and interactive elements that allow employees to learn independently, thus maximizing knowledge transfer and improving skills in various fields. Survey results after testing by users through user acceptance test activities show that on the Ease of Navigation aspect, 55% of respondents stated “strongly agree” the application is easy to use”. The aspect of Confidence in Application Capabilities, the results are 55% of respondents “strongly agree” this application believes it can improve HR skills and abilities. For the Quality of Main Features, 36% of respondents stated “strongly agree” the main features in this application are easy to use and the remaining 64% stated “agree”. On the aspect of Impact on HR Improvement, 46% of respondents “strongly agree” this application has a positive impact and the remaining 54% of respondents stated “agree”. Finally, on the aspect of Benefit for the Company, 36% of respondents “strongly agree” that this application is useful and the remaining 64% stated “agree”. This platform can be accessed across all business sectors so that it becomes a strategic tool that helps Transportation Company X achieve its goals and improve its public transportation services.